Altered expression of glycobiology-related genes in Parkinson’s disease brain - Schneider, Jay S.; Singh, Garima (Frontiers in Molecular Neuroscience, 2022)
The precise mechanisms initiating and perpetuating the cellular degeneration in Parkinson’s disease (PD) remain unclear. There is decreased expression of the main brain gangliosides, and GM1 ganglioside in particular, in the PD brain along with decreased expression of the genes coding for the glycosyltranferase and the sialyltransferase responsible for the synthesis of these brain gangliosides. However, potentially important pathogenic mechanisms contributing to the neurodegeneration in PD may also include altered levels of expression of genes involved in glycosylation, sialylation and sphingolipid synthesis and metabolism. Although various studies have described pathological lipid and glycolipid changes in PD brain, there have been limited studies of expression of glycobiology-related genes in PD brain. The current study was performed as an initial attempt to gain new information regarding potential changes in glycoprotein and glycolipid-related genes in PD by investigating the gene expression status for select glycosyltransferases, sialyltransferases, sialidases, sphingosine kinases, and lysosomal enzymes in the substantia nigra and putamen from patients with PD and neurologically normal controls. Results showed altered expression of glycosyltransferase genes (B3GALT2 and B4GALT1) potentially involved in microglial activation and neuroinflammation, sphingosine-1-phosphate (S1P) modulators (SPHK1, SPHK2, and SGPL1) involved in sphingolipid synthesis and metabolism, polysialyltransferase genes (ST8SIA2 and ST8SIA4) that encode enzymes responsible for polysialic acid (polySia) biosynthesis, and the sialidase NEU4, expression of which has been linked to the clearance of storage materials from lysosomes. The data presented here underscore the complexity of the glycolipid/sphingolipid dysregulation in the PD brain and continued and expanded study of these processes may not only provide a greater understanding of the complex roles of aberrant glycosylation sialylation, and sphingolipid synthesis/metabolism in the pathophysiology of PD but may identify potential druggable targets for PD therapeutics.